PENYELESAIAN SENGKETA PENANAMAN MODAL MELALUI ARBITRASE INTERNASIONAL - Nur Hidayat Fadhillah; Pauzan; Zulfikri Toguan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
International arbitration as a mechanism for resolving investment disputes has evolved into the most preferred forum by foreign investors in settling disputes with host states, offering advantages of neutrality, arbitrator expertise, procedural speed, and certainty of award enforcement through international conventions. This normative study analyzes three key issues, namely the legal framework of international arbitration in resolving investment disputes in Indonesia, the international arbitration mechanisms available to foreign investors, and the legal implications of international arbitration awards on Indonesia's investment legal system. The approach employed is a statutory approach and a conceptual approach by examining various national regulations, international conventions, and relevant academic literature. The results indicate that Indonesia has built a sufficiently adequate international arbitration legal framework but still faces challenges in terms of consistency in implementing bilateral investment treaties, capacity for handling investment disputes, and balancing investor protection with state regulatory sovereignty. This study recommends a systematic review of all Indonesia's bilateral investment treaties as a strategic step to strengthen the state's legal position in international arbitration disputes.